Clinical Manifestations Associated with Overweight/Obesity in Puerto Ricans with Fibromyalgia Syndrome - Ruth M. Fred-Jiménez; Mariangelí Arroyo-Ávila; Ángel M. Mayor; Grissel Ríos; Luis M. Vilá (Hindawi Limited, 2016)
Objective. To determine the clinical manifestations associated with overweight/obesity in Hispanics from Puerto Rico with fibromyalgia syndrome (FMS). Methods. A cross-sectional study was performed in 144 patients with FMS (per American College of Rheumatology (ACR) classification criteria). Sociodemographic features, FMS-related symptoms, tender points (per ACR criteria), comorbidities, and FMS treatment were examined. BMI was calculated and patients were grouped into two categories: BMI ≤ 24.9 kg/m2 (nonoverweight/obese) and BMI ≥ 25 kg/m2 (overweight/obese). Bivariate and multivariate analyses were used to evaluate differences between the study groups. Results. The mean (standard deviation (SD)) age of patients was 50.2 (9.9) years; 95.1% were females and 75.7% were overweight/obese. In the bivariate analysis, overweight/obese patients were more likely to have self-reported memory impairment, anxiety, shortness of breath, and urinary frequency than nonoverweight/obese patients. In addition, the tender point count was higher in the overweight/obese group. In the logistic regression analyses, self-reported memory impairment and urinary frequency differences remained significant after adjusting for confounding variables. Conclusion. In this population of Puerto Ricans with FMS, overweight/obese patients experienced more FMS-related manifestations than nonoverweight/obese individuals. However, prospective studies are needed to confirm these associations and to elucidate if weight reduction interventions could favorably impact the severity of FMS.